2020
DOI: 10.3344/kjp.2020.33.2.138
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of preoperative ultrasound guided fascia iliaca block versus femoral nerve block for proximal femur fractures before positioning for spinal anesthesia: an observational study

Abstract: Background: Severe pain associated with proximal femur fractures makes the positioning for regional anesthesia a challenge. Systemic administration of analgesics can have adverse effects. Individually, both the fascia iliaca block (FIB) and femoral nerve blocks (FNB) have been studied. However, there is little evidence comparing the two. The aim of this study was to compare the overall efficacy of the two blocks in patients with proximal femur fracture before positioning for spinal anesthesia. Methods: ASA (Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
(34 reference statements)
1
2
1
Order By: Relevance
“…9 Gupta et al reported significant VAS reduction after 5 minutes in a group receiving US-guided FNB in fracture femur surgeries. 5 Similarly, in the present study we found earlier pain relief at 5 and 10 minutes in US-guided FNB as compared to NS-guided FNB. This was probably because of accurate drug deposition around the femoral nerve compared to blind placement in the case of group NS.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…9 Gupta et al reported significant VAS reduction after 5 minutes in a group receiving US-guided FNB in fracture femur surgeries. 5 Similarly, in the present study we found earlier pain relief at 5 and 10 minutes in US-guided FNB as compared to NS-guided FNB. This was probably because of accurate drug deposition around the femoral nerve compared to blind placement in the case of group NS.…”
Section: Discussionsupporting
confidence: 85%
“…4 The duration of analgesia with US-guided FNB was 5.2 hours in the study by Gupta et al, whereas we had 7.7 hours, the difference may be due to the use of different local anaesthetics. 5 Singh et al found the duration of analgesia to be 6 hours with nerve stimulating technique of FNB using 0.2% ropivacaine, whereas it was 4.7 hours in our study. 12 This may be due to the additive effect of 0.75% ropivacaine used intra-spinally and top-ups of 0.2% ropivacaine used intraoperatively by them.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…[5][6][7][8] However, the literature has suggested that these blocks do not cover the ON sufficiently 12,13 and carry a high risk of quadriceps weakness. [14][15][16][17] An ultrasound-guided suprainguinal ligament approach to the fascia iliaca compartment has proven better spread of local anaesthetics to the ON located medial to the psoas muscle. However, it also weakens the muscle strength of the operated leg, delaying optimal rehabilitation.…”
mentioning
confidence: 99%